External validation of the HCM Risk-Kids model for predicting sudden cardiac death in childhood hypertrophic cardiomyopathy. (31st October 2021) - Norrish, Gabrielle; Qu, Chen; Field, Ella; Cervi, Elena; Khraiche, Diala; Klaassen, Sabine; Ojala, Tiina H; Sinagra, Gianfranco; Yamazawa, Hirokuni; Marrone, Chiara; Popoiu, Anca; Centeno, Fernando; et al.
Abstract: Aims: Sudden cardiac death (SCD) is the most common mode of death in childhood hypertrophic cardiomyopathy (HCM). The newly developed HCM Risk-Kids model provides clinicians with individualized estimates of risk. The aim of this study was to externally validate the model in a large independent, multi-centre patient cohort. Methods and results: A retrospective, longitudinal cohort of 421 patients diagnosed with HCM aged 1–16 years independent of the HCM Risk-Kids development and internal validation cohort was studied. Data on HCM Risk-Kids predictor variables (unexplained syncope, non-sustained ventricular tachycardia, maximal left ventricular wall thickness, left atrial diameter, and left ventricular outflow tract gradient) were collected from the time of baseline clinical evaluation. The performance of the HCM Risk-Kids model in predicting risk at 5 years was assessed. Twenty-three patients (5.4%) met the SCD end-point within 5 years, with an overall incidence rate of 2.03 per 100 patient-years [95% confidence interval (CI) 1.48–2.78]. Model validation showed a Harrell's C -index of 0.745 (95% CI 0.52–0.97) and Uno's C -index 0.714 (95% 0.58–0.85) with a calibration slope of 1.15 (95% 0.51–1.80). A 5-year predicted risk threshold of ≥6% identified 17 (73.9%) SCD events with a corresponding C -statistic of 0.702 (95% CI 0.60–0.81). Conclusions: This study reports the first external validation of the HCM Risk-Kids model in a large and geographically diverse patient population. A 5-year predicted risk of ≥6% identified over 70% of events, confirming that HCM Risk-Kids provides a method for individualized risk predictions and shared decision-making in children with HCM.